Analisis Pendapatan Operator Perahu Wisata Hiu Paus Serta Tantangan Operasionalnya di Desa Botubarani Teluk Tomini - Dhea Farandina S. Tatang; Azis Salam; Abdul Hafidz Olii (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Whale shark boat operators are people or organizations that manage and operate boats for tourism purposes that involve interaction with whale sharks. The basis of this study was conducted to analyze the income earned by whale shark boat operators and their operational challenges. Several factors that need to be considered include the number of tourists, the rates charged by the operator, and the operational costs that must be borne. The purpose of this study is to analyze the income and evaluate challenges faced by whale shark tour boat operators. This study uses descriptive survey and observation methods using primary and secondary data, and quantitative income analysis, to identify respondents using the census sampling method. Based on the results of the study, the average net income of whale shark tour boat operators in Botubarani is Rp. 11,710,000 per year. As for the operational challenges in developing whale shark tourism, there are 3 things that affect income, namely the appearance of whale sharks, weather factors, number of visitors, and when there are fewer or no visitors during the wind and wave season which results in no income because whale sharks do not appear on the surface of the water